Environmental water flows go global to support implementation of the Sustainable Development Goals (SDGs) (WLE-IWMI) - CGIAR Research Program on Water, Land and Ecosystems (2018)
CGIAR Research Program on Water, Land and Ecosystems (WLE) and partners have been leading efforts to include environmental flows (e-flows) in the SDG Indicator 6.4.2 on water stress. WLE led the preparation of a guideline to support countries’ reporting on e-flows. This methodology is being distributed by the Food and Agriculture Organization of the United Nations (FAO) to all countries to monitor progress on SDG 6.4 on alleviating water scarcity.